Emotional Development in Adults with Autism and Intellectual Disabilities: A Retrospective, Clinical Analysis - Sappok, T.; Budczies, J.; Bolte, Sven; Dziobek, I.; Dosen, A.; Diefenbacher, A. (Public Library of Science, 2013)
Individuals with intellectual disability (ID) are at risk for additional autism spectrum disorders (ASD). A large amount of research reveals deficits in emotion-related processes that are relevant to social cognition in ASD. However, studies on the structure and level of emotional development (ED) assessing emotional maturity according to the normative trajectory in typically developing children are scares. The level of ED can be evaluated by the 'Scheme of Appraisal of Emotional Development' (SAED), a semi-structured interview with a close caregiver. The SAED assesses the level of emotional developmental based on a five stage system in 10 domains, for example, 'interaction with peers' or 'object permanence', which are conducive to the overall emotional developmental level. This study examined the ED as measured by the SAED in 289 adults (mean age: 36 years) with ID with and without additional ASD. A lower level in ED was observed in ASD/ID combined that corresponded to the ED of typically developing children aged 1.5-3 years versus an ED with a corresponding age of 3-7 years in ID individuals without ASD. Moreover, distinct strengths in 'object permanence', and weaknesses in 'interaction', 'verbal communication', 'experience of self', 'affect differentiation', 'anxiety', and 'handling of material objects' led to a characteristic pattern of ED in ASD. SAED domains with highest discriminative power between ID individuals with and without ASD (5/10) were used to predict ASD group membership. The classification using a selection of SAED domains revealed a sensitivity of 77.5% and a specificity of 76.4%. ASD risk increased 2.7-fold with every SAED level. The recognition of delayed and uneven pattern of ED contributes to our understanding of the emotion-related impairments in adults with ID and ASD these individuals. Assessment of intra-individual ED could add value to the standard diagnostic procedures in ID, a population at risk for underdiagnosed ASD. © 2013 Sappok et al.